Comparison of two rapid methods for detection of respiratory syncytial virus (RSV) (Testpack RSV and ortho RSV ELISA) with direct immunofluorescence and virus isolation for the diagnosis of pediatric RSV infection. - Thomas, E E (1991)
The ability of two commercial immunoassays to detect respiratory syncytial virus (RSV) in respiratory specimens was evaluated as follows: 152 specimens were tested by TestPack RSV (Abbott), and 72 were tested by Ortho RSV ELISA (Ortho). Test outcomes were compared with those of virus isolation alone, direct immunofluorescence assay (DFA) alone, or virus isolation and/or DFA. TestPack RSV versus virus isolation showed 91% sensitivity, 96% specificity, 93% positive predictive value (PPV), and 95% negative predictive value (NPV). TestPack RSV versus DFA showed 89% sensitivity, 97% specificity, 96% PPV, and 93% NPV. When TestPack RSV performance was compared with that of virus isolation and DFA, the sensitivity was 87% and the specificity was 100%. Ortho RSV ELISA versus virus isolation showed 88% sensitivity, 87% specificity, 79% PPV, and 93% NPV. Ortho RSV ELISA versus DFA showed 91% sensitivity, 88% specificity, 81% PPV and 95% NPV. When Ortho RSV ELISA performance was compared with that of virus isolation and DFA, the sensitivity was 86%, the specificity was 89%, the PPV was 86%, and the NPV was 89%. The accuracy of the TestPack RSV in combination with ease of performance and no need for specialized equipment or special skills make it an attractive alternative to DFA for rapid direct detection of RSV.